The university campus as a modern urban project. The case of the Sausalito Campus (UCV) in Viña del Mar (1968-1971) - Braghini, Anna (CIAN-Revista de Historia de las Universidades, 2025)
This article analyzes the unbuilt proposal for the Sausalito University Campus of the Pontificia Universidad Católica de Valparaíso (CUS-UCV), developed between 1968 and 1971 within the context of the Chilean University Reform. The research investigates to what extent this proposal constituted an innovation in terms of urban integration and academic reorganization, and what kind of territorial vision it projected compared to other university campus models developed in Chile during the same period. The central hypothesis argues that the CUS-UCV was not merely a response to increased student enrollment and institutional transformation, but rather an advanced territorial planning strategy that linked academic function with urban expansion for the city of Viña del Mar. The main objective of the study is to understand how the principles of the University Reform were translated into a campus proposal conceived as an urban operation. The research adopts a qualitative methodology with a historical-comparative approach, based on primary sources such as the original report by architect Arturo Baeza –submitted in 1971 to Rector Raúl Allard and preserved in the José Vial Armstrong Historical Archive– as well as an interview conducted by the author with the former rector. The study is further supported by a comparative analysis with the Playa Ancha Campus of the Universidad de Chile (1962-1967), contextualizing planning strategies of that era. Grounded in the theoretical frameworks of urban project and typology, the CUS-UCV is interpreted not as a collection of functional buildings, but as an open, territorial system capable of structuring future urban transformations. The project draws upon principles previously explored by the UCV School of Architecture, particularly in proposals such as Achupallas and the Naval School, articulating infrastructure, topography, and institutional organization. Although never built, the CUS-UCV provides a complex and alternative perspective on the role of the university in shaping urban space in Chile during the second half of the twentieth century.